Blockage of SLC31A1‐dependent copper absorption increases pancreatic cancer cell autophagy to resist cell death. (31st January 2019) - Yu, Ze; Zhou, Rongtao; Zhao, Yicheng; Pan, Yi; Liang, Hao; Zhang, Jin‐San; Tai, Sheng; Jin, Liang; Teng, Chun‐Bo
Abstract: Objectives: Clinical observations have demonstrated that copper levels elevate in several cancer types, and copper deprivation is shown to inhibit tumour angiogenesis and growth in both animal models and preclinical trials. However, the content of copper in pancreatic duct adenocarcinoma (PDAC) and whether it is a potential therapy target is still unknown. Materials and Methods: The levels of copper in PDAC specimens were detected by ICP‐MS assays. Copper depletion in Panc‐1 or MiaPaCa‐2 cells was conducted via copper transporter 1 (SLC31A1) interference and copper chelator tetrathiomolybdate (TM) treatment. The effects of copper deprivation on cancer cells were evaluated by cell proliferation, migration, invasion, colony formation and cell apoptosis. The mechanism of copper deprivation‐caused cancer cell quiescence was resolved through mitochondrial dysfunction tests and autophagy studies. The tumour‐suppression experiments under the condition of copper block and/or autophagy inhibition were performed both in vitro and in xenografted mice. Results: SLC31A1‐dependent copper levels are correlated with the malignant degree of pancreatic cancer. Blocking copper absorption could inhibit pancreatic cancer progression but did not increase cell death. We found that copper deprivation increased mitochondrial ROS level and decreased ATP level, which rendered cancer cells in a dormant state. Strikingly, copper deprivation caused an increase in autophagy to resist death of pancreatic cancer cells. Simultaneous treatment with TM and autophagy inhibitor CQ increased cell death of cancer cells in vitro and retarded cancer growth in vivo. Conclusions: These findings reveal that copper deprivation‐caused cell dormancy and the increase in autophagy is a reason for the poor clinical outcome obtained from copper depletion therapies for cancers. Therefore, the combination of autophagy inhibition and copper depletion is potentially a novel strategy for the treatment of pancreatic cancer and other copper‐dependent malignant tumours.